Investigating the impact of service quality dimensions on reputation and brand trust - Majid Esmaeilpour; Amrollah Sayadi; Mahnaz Mirzaei (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2017)
Purpose: The objective of this study was to investigate the impact of service quality dimensions on brand reputation and brand trust in Iran's Saderat Bank. Design/methodology/approach: The present study is applied in terms of objective and results of study and correlational type of descriptive-survey in terms of nature and method of implementation. The Study Population included customers of Iran's Saderat Bank branches in Bushehr city. Since the population size was large, convenient sampling was used and 400 questionnaires were distributed among the customers of the bank. Structural equation modeling was used to analyze the data through Smart PLS software. Findings: The findings reveal that all dimensions of service quality (tangible factors, reliability, accountability, trustworthiness, and empathy) have a positive and significant impact on brand trust and brand reputation. Research limitations/implications: - The population of the research was limited to Bushehr city (Iran). Other limitations relates to the data collection tool; the questionnaire has some disadvantages that can influence results. Therefore, we should be cautious in generalizing the findings. Originality/value: This research examines the impact of service quality dimensions and the level of impact of each dimension on brand reputation and trust, in order to identify the dimensions of service quality affecting brand reputation and trust, and to use them in branding. Thus, implementing the suggested actions to enhance the quality of services will have a positive impact on enhancing the brand reputation and brand trust in the banking industry.
Keywords: M31; D12; D22; 330; Service; Service Quality Dimensions; Brand Reputation; Brand Trust; Saderat Bank of Iran